Congenital left ventricular aneurysm diagnosed with atrial septal defect. (June 2019) - Kobayashi, Yasuyuki; Kotani, Yasuhiro; Kuroko, Yosuke; Arai, Sadahiko; Kasahara, Shingo
An 8-year-old girl with no history of chest pain or exertional dyspnea was admitted for atrial septal defect closure. Transthoracic echocardiography showed a sac in the right atrium, protruding from the left ventricle. A left ventricular aneurysm was confirmed by cardiac catheterization. At surgery, the protruding saccular aneurysm arising from the left ventricle was located between the atrial septal defect and the tricuspid valve. We closed the orifice with interrupted sutures from the right atrium. The atrial septal defect was closed with an autologous pericardial patch. Histology showed the aneurysmal wall had no myocardial layer, being replaced by fibrous tissue.